Cardiotoxicity of CPX-351 in children and adolescents with relapsed AML: a Children's Oncology Group report - Leger, Kasey J.; Absalon, Michael J.; Demissei, Biniyam G.; Smith, Amanda M.; Gerbing, Robert B.; Alonzo, Todd A.; Narayan, Hari K.; Hirsch, Betsy A.; Pollard, Jessica A.; Razzouk, Bassem I.; Getz, Kelly D.; Aplenc, Richard; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Anthracyclines are effective in treating acute myeloid leukemia (AML) but limited by cardiotoxicity. CPX-351, a liposomal daunorubicin and cytarabine, may provide therapeutic benefit with less cardiotoxicity. Acute changes in left ventricular systolic function and cardiac biomarkers were evaluated after a cycle of CPX-351 in children with relapsed AML treated on the phase 1/2 Children's Oncology Group study, AAML1421. Methods Subjects received 135 units/m2/dose of CPX-351 on days 1, 3, and 5 as cycle 1. Echocardiograms were performed and centrally quantitated at baseline and at the end of cycle 1 (day 29 +/− 1 week). High sensitivity troponin (hs-cTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) were measured at baseline and serially through the end of cycle 1 (days 5, 8, 15, 22 and 29). Differences between baseline and post-CPX-351 echo/biomarker measures were analyzed using Wilcoxon signed rank tests. Linear regression was used to model post-CPX-351 left ventricular ejection fraction (LVEF) with cTnT/NT-proBNP at each time point, controlling for baseline LVEF. Cancer therapy related cardiac dysfunction (CTRCD) was defined as a decline in LVEF of ≥10%–<50%. Results Twenty-five of 38 heavily anthracycline pre-treated (median 348 mg/m2 daunorubicin equivalents) subjects enrolled on AAML1421 were included in the cardiac analyses. At baseline, centrally quantitated LVEF was <50% in 8 of 25 subjects (32%) with a median LVEF of 53.8% [48.0, 56.9]. Following CPX-351, LVEF declined significantly (ΔLVEF −3.3% [−7.8, 0]) and 6 of 25 subjects (24%) experienced CTRCD. Amongst all subjects, hs-cTnT was modestly increased at end of cycle 1 compared to baseline [baseline hs-cTnT 7.2 (3, 10.6); ΔcTnT 1.80 (0, 6.1), p = 0.03]. NT-proBNP remained stably elevated without significant change. No significant associations were seen between NT-proBNP or cTnT levels and post-CPX-351 LVEF. Discussion In this single arm study of anthracycline pre-treated children exposed to CPX-351, baseline abnormalities in cardiovascular function were prevalent. Following CPX-351, LVEF decreased, cTnT increased, and NT-proBNP did not change. Longer follow-up is needed to determine whether these changes result in clinically meaningful long-term decrements in cardiac function. An ongoing randomized trial of CPX-351 compared to standard anthracyclines in anthracycline naïve patients will provide further insight into the cardiac effects of CPX-351 (ClinicalTrials.gov; NCT04293562).